2021
DOI: 10.3389/fnhum.2021.701872
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Match Between Observed and Own Bodies, but Not Its Accuracy, Is Influenced by Movement Dynamics and Clothing Cues

Abstract: Own-perceived body matching – the ability to match one’s own body with an observed body – is a difficult task for both general and clinical populations. Thus far, however, own-perceived body matching has been investigated in situations that are incongruent with how we are used to experience and perceive our body in daily life. In the current study, we aimed to examine own-perceived body matching in a context that more closely resembles real life. More specifically, we investigated the effects of body movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 111 publications
(156 reference statements)
0
3
0
Order By: Relevance
“…The MAIA have shown adequate internal consistency (Cronbach’s alpha 0.64 to 0.83 for all subscales) X Auditory trials Presented in four conditions: an anchor task (20 trials); a practice task (3 trials); an experimental block (30 trials) and a questionnaire block (3 trials) X X Estimation of body position (finger/waist) To assess estimation of location or position of fingertip/knuckle (allowing to calculate the estimated finger length can be calculated) and waist width after each auditory experimental trial X Confidence task It has been found that the reliability of perception might be linked to subjective rather than objective accuracy [ 41 ]. For example, previous studies using body illusions report that confidence was not accompanied by increases in objective accuracy (i.e., [ 42 , 43 ]). Therefore, to assess the reliability of their estimations, after each auditory experimental trial, the feeling of confidence with the estimation of body part position will be explicitly assessed by asking the participants: “From one to seven, how confident are you of your estimation?” (7-point Likert scale) X X Body feelings questionnaire (finger/waist) [ 25 ] To assess subjective feelings about their finger/waist after the trials (susceptibility to the illusion).…”
Section: Participantsmentioning
confidence: 99%
“…The MAIA have shown adequate internal consistency (Cronbach’s alpha 0.64 to 0.83 for all subscales) X Auditory trials Presented in four conditions: an anchor task (20 trials); a practice task (3 trials); an experimental block (30 trials) and a questionnaire block (3 trials) X X Estimation of body position (finger/waist) To assess estimation of location or position of fingertip/knuckle (allowing to calculate the estimated finger length can be calculated) and waist width after each auditory experimental trial X Confidence task It has been found that the reliability of perception might be linked to subjective rather than objective accuracy [ 41 ]. For example, previous studies using body illusions report that confidence was not accompanied by increases in objective accuracy (i.e., [ 42 , 43 ]). Therefore, to assess the reliability of their estimations, after each auditory experimental trial, the feeling of confidence with the estimation of body part position will be explicitly assessed by asking the participants: “From one to seven, how confident are you of your estimation?” (7-point Likert scale) X X Body feelings questionnaire (finger/waist) [ 25 ] To assess subjective feelings about their finger/waist after the trials (susceptibility to the illusion).…”
Section: Participantsmentioning
confidence: 99%
“…1 in the survey included a question about confidence reaching the requested position (i.e., position 1 or 2), "How confident were you with this sound that your arm was in the <position>? ", which was based on previous research assessing task confidence [57][58][59] . Participants answered using a 7-point Likert-type scale, ranging from 1: "not confident at all" to 7: "completely confident".…”
Section: Effects Of Change On Pitch On Bodily and Emotional Feelingsmentioning
confidence: 99%
“…It has been found that the reliability of perception might be linked to subjective rather than objective accuracy [40]. For example, previous studies using BIs report that con dence was not accompanied by increases in objective accuracy (i.e., [41,42]). Therefore, to assess the reliability of their estimations, after each auditory experimental trial, the feeling of con dence with the estimation of body part position will be explicitly assessed by asking the participants: "From one to seven, how con dent are you of your estimation?"…”
Section: Con Dence Taskmentioning
confidence: 99%